Analysis of PTKIN Domain Security in West Sumatra Based on Spam Score, Cloudflare, and Backlink - Muhammad Rahfiqa Zainal; Ihdi Syahputra Ritonga; Ahmad Zaki; Agus Sundari (UIN Imam Bonjol Padang, 2026)
This study investigates the security and digital reputation posture of three State Islamic Universities (UIN) in West Sumatra—UIN Imam Bonjol (uinib.ac.id), UIN Mahmud Yunus (uinmy.ac.id), and UIN Sjech M. Djamil Djambek Bukittinggi (uinbukittinggi.ac.id)—using externally observable indicators during December 1–15, 2025. The assessment integrates third‑party domain reputation metrics (Moz Spam Score, Domain/Page Authority, backlink volume, and toxic backlink ratio) with passive network inspection to identify Cloudflare reverse‑proxy/WAF adoption and the negotiated TLS protocol version. Data are analyzed descriptively and through inferential modeling, including Pearson correlation between Cloudflare activation (binary) and Spam Score, and K-Means clustering to classify institutional risk into low, medium, and high zones. Results show substantial disparity: UIN Imam Bonjol exhibits a healthy Spam Score (2%) with Cloudflare enabled and TLS 1.3, whereas UIN Bukittinggi records a critical Spam Score (45%) and a high toxic backlink ratio (7.3%) without Cloudflare. Correlation analysis indicates a strong inverse association between Cloudflare activation and Spam Score (r = −0.89). Forensic backlink inspection identifies SEO poisoning patterns on vulnerable academic subdomains, dominated by gambling-related anchors (45%) and adult content (20%). The proposed risk zoning supports targeted recommendations, including WAF standardization, OJS hardening and patching, content moderation, and the cleanup or disavowal of toxic backlinks to protect the institutional reputation.